Requirements of Consent and Innocence and its Impact on Medical Liability Falling: Requirements of consent and innocence - Abbasi, Mahmoud (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: The theory of consent and innocence are two major approaches in medical law that, studying them as one of the essential conditions of medical liability, has special significance. This study aimed to analyze the discussion of consent and innocence and its impact on medical liability falling. Materials and Methods: In the present study, keywords of consent, innocence, doctor, and liability in databases PubMed, Magiran, SID, ISC, and Google Scholar were searched and relevant literature was searched and analyzed. Ethical Considerations: Principles of ethics and integrity in the search, citation, and literature analysis were taken into consideration. Findings: In this study, after explaining the concept of patient consent and satisfactory and capacity conditions in its declaration and also the concept of innocence and its terms, it is emphasized that every wise and mature person has the right to decide about the treatment or medical method recommended for him. Conclusion: Although the legislator explicitly pointed to obtain consent from the patient or his legal representatives in surgeries and medical operations and the existence of such consent in all surgical and medical operations is known as a requirement except in cases of urgent, but because in our legal system to comply with Jurisprudence, the obligation to result in surgeries and medical operations indicates the nature of the commitment of doctors and theoretical basis of medical liability, obtaining patient consent, legitimation of medical procedures and respecting the legitimacy of scientific and technical aspects of the state system are not the complete reasons of the collapse of medical liability and compensation the physician is responsible for a compensation of the damages applied to the patient unless before starting treatment acquittal is received from the patient or his representatives. *Corresponding Author: Mahmoud Abbasi; Email: dr.abbasi@sbmu.ac.ir; ORCID: https://orcid.org/0000-0002-4223-6818 Please cite this article as: Abbasi M. Requirements of Consent and Innocence and its Impact on Medical Liability Falling. Bioeth Health Law J. 2021; 1:1-8: (e7). http://doi.org/10.22037/bhl.v1i1.38132